Comparative analysis of the effects of combined spinal epidural anesthesia versus psoas compartment and sciatic nerve block for partial hip prosthesis in the geriatric population - Mustafa Ozden, Mehmet; Cesur, Mehmet; Emeli, Yusuf; Sevimli, Resit (Annals of Medical Research, 2021)
Aim: We aimed to compare combined spinal-epidural anesthesia (CSE) and combined psoas compartment & sciatic nerve block (PCSNB) peripheral nerve blocks, in terms of intraoperative and postoperative pain, hemodynamics and side effects in geriatric population who underwent partial hip prosthesis.Material and Methods: A total of 50 patients who underwent elective partial hip prosthesis and PCSNB or CSE were included. The age range was between 60-99 years and ASA scores were ≤ 3. Twenty-five patients underwent CSE anesthesia with 1 mL plain bupivacaine, while PCSNB and iliac crest blocks were employed in 25 patients. Perioperative anesthetic efficacy, blood pressures, pulse rates, saturation values, need for postoperative analgesia and side effects were compared. Results: At the end of the operation, the mean arterial pressure was lower in both groups compared to the baseline (initial) values and the decline in the CSE group was statistically significant. Hypotension was detected in 11 patients (44%) in the CSE group and 2 patients (8%) in the PCSNB group. Effective analgesia was provided in all patients in the CSE group, while 5 patients (20%) required additional analgesic medications through the epidural catheter in the follow-up. The first postoperative analgesic hour was remarkably longer in the PCSNB group (4.84 ± 2.54 hours vs. 1.64 ± 0.9 hours).Conclusion: Our data demonstrated that the combination of the psoas compartment, parasacral, sciatic and iliac crest blocks provides effective analgesia and maintains hemodynamic stability after hip prosthesis operations in elderly patients.
Keywords: Hip prosthesis; combined anesthesia; psoas compartment block; sciatic nerve block; postoperative analgesia